Analisis Perbandingan Harga Saham dan Volume Perdagangan Saham Sebelum dan Sesudah Stock Split Pada Masa Pandemi - Mengga, Grace Sriati Mengga; Batara, Mince (UKI Toraja Press, 2021)
In this study, a comparison of stock prices before and after a stock split and a comparison between trading volume and after a stock split was carried out during the Pandemic period. A stock split is one of the actions taken by a company to increase its shares and make the shares more liquid again. Based on the analysis in this study, it was found that there was a significant difference between stock prices before and after the stock split and a significant difference was also found between the trading volume of shares before and after the stock split. Researchers found 11 companies that carried out stock splits during the pandemic in December 2019-September 2021. The observation period for companies that carried out stock splits was 5 days before and 5 days after the announcement of the stock split, so in the test using the average value of the stock price and the average value -average of trading volume. In this study, the normality test was used to see if the data were normally distributed and the two-sample difference test was paired t-test or t-test.